Unmet need for family planning and associated factors among currently married women in Hawella Tulla subcity, Hawassa, southern Ethiopia: community-based study - Abiyu Ayalew Assefa; Samson G. Selassie; Abebayehu Mesele; Henok Bekele Kebede; Anteneh Fikrie; Geleta Abera (BMC, 2023)
Abstract Background The unmet need for family planning remains a major public health concern in developing countries, especially in sub-Saharan Africa. Similarly, in Ethiopia, the unmet need for family planning is considerably high. However information regarding associated factors of unmet need of family planning is limited, the study area in particular. Thus, this study was aimed at assessing unmet family planning and associated factors among currently married women in Hawella Tulla Subcity. Methods A community based cross-sectional study was employed on 436 currently married women. Both bivariable and multivariable logistic regression model were used and having P-value of < 0.05 was considered as independently associated factors. Strength of association of the variable was described using adjusted odd ratios with their 95% confidence interval. Result The overall unmet need for family planning among currently married women was found to be 18.1% (95% CI: 14.5%, 21.8%). Having age of below 18 years at first marriage AOR = 1.95 (95% CI: 1.14, 3.33), woman's not attained formal education AOR = 2.23 (95% CI: 1.02, 4.84), women whose partner had non-supportive for family planning use AOR = 2.32 (95% CI: 1.35, 3.99) and women without media access AOR = 2.13 (95% CI: 1.19, 3.81) were significantly associated with increasing unmet need for family planning. Conclusions Despite the presence of high family planning services coverage in the study area, the magnitude of unmet need for family planning is still reasonably high. Having age of below 18 years at first marriage, woman's not attained formal education, women whose partner had non-supportive for family planning use and inavailability of media access in the house were found to be associated with high unmet need for family planning. Therefore, efforts are needed to empower women through education, avoiding early marriage and encouraging couple-based family planning interventions. Increasing media access is also advisable intervention.